Design of the Wisconsin Card Sorting Test (WCST) computerized version: Theoretical Fundamental, Developing and Psychometrics Characteristics - M. Shahgholian (Muṭāli̒āt-i Ravān/Shināsī-i Bālīnī, 2012)
Executive functions describe as higher level processes that controlling and monitoring elementary (object) mental operations Neuroimaging studies have identified some of cortical areas involved in executive functions, frontal and prefrontal mostly. Because of these processing occur in a proportional second, those couldn’t be tested by traditional paper-pencil tools exactly. With introducing computers as a valuable tool for psychological and neuropsychological assessment, developing computerized version of tests to be extensive. Since according to researches, the wisconsin card sorting test is one of the most distinctive test for frontal and prefrontal executive functions, in present study, we effort to design and developing wisconsin computerized version based on a standard version.For differential validity, according to scores of Revised Eysenck Personality Questionnaire (EPQ-R), 2 groups including high anxiety (Anx+) and low anxiety (Anx-) were selected and performed computerized version of wisconsin. The results indicated that means of outputs differ in 2 groups. Also, cronbach’s alpha and split-half coefficients of computerized version showed that it has suitable reliability in Iranian subjects.